Studi Perencanaan Sarana Air Bersih Melalui Sistem Perpipaan di Desa Marmoyo, Kecamatan Kabuh, Kabupaten Jombang - Hartadi, Agus; Saves, Faradlillah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The availability of clean water is mandatory and applies to all places. Marmoyo Village is part of Kabuh District, Jombang Regency which relies on shallow wells to meet its clean water needs. To find out the projected water demands of the population is a population calculation projection. To find out the planning average of clean water demands by pumping tests to find out the maximum discharge of deep wells and the optimum discharge of pumping as well as the planned piping scheme using the Epanet 2.2 program to find out the flow rate, velocity, pressure and headloss. The research results showed that the average discharge requirement in 2044 was 1,163 l/second for a population in 2044 of 1,395 people. Meanwhile, the maximum discharge for deep wells obtained through pumping tests was 1.64 l/second. The piping system uses a double system and a branch system with 2